Effect Of Wind On The Crop Water-Stress Index Derived By Infrared Thermometry - O'Toole, J.C.; Hatfield, J.L. (Wiley, 1983)
A new plant or crop water stress index (CWSI) that depends on interpreting crop or foliage‐to‐air temperature differential (Tf‐Ta) shows promise in both research and irrigation water management. The method relies on the unique relation between Tf‐Ta, and atmospheric water vapor pressure deficit (VPD). However, the method of estimating the upper limit of Tf‐Ta, a critical step in CWSI calculation, was questionable and lacked field validation. We measured the upper limit of Tf‐Ta, and attendant micrometeorological variables on severely water stressed sorghum (Sorghum bicolor L.), corn (Zea mays L.), and bean (Phaseolus vulgaris L.) grown on a Typic Xerotherent, and cotton (Gossypium hirsutum L.) grown on a Typic Torriorthent. Actual measured values of the upper limit of Tf‐Ta ranged from 2.5 to 8.5 °C across crops. The poor agreement between actual and calculated values was analyzed with respect to net radiation, VPD, and windspeed. Windspeed was found to be the primary factor causing erroneous estimation of the upper limit of Tf‐ Ta, and hence CWSI values. Crop water stress index values measured at low windspeed overestimated the level of water stress while those measured at high windspeed underestimated it. Crop specific changes in the boundary layer resistance‐windspeed relationship partially explain the discrepancy between measured and calculated Tf‐Ta, upper limit values. Modification of the CWSI to account for the influence of windspeed is discussed.